HUBUNGAN DERAJAT PERLEMAKAN HATI NON-ALKOHOLIK DENGAN AKTIVITAS AMINOTRANSFERASE SERUM - Nyoman Trisna Yustiani; Mutmainnah .; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
Fatty liver could be related to alcoholic or non-alcoholic. Mild to moderate elevation of serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities are the most laboratories test ordered in patient with non-alcoholic fatty liver. This studyhas purposed to know the relation of degree non-alcoholic fatty liver’s with aminotransferase serum activity. A cross-sectional studywas done in 38 patients with non-alcoholic fatty liver aged 30 to 60 years at Clinical Pathology Laboratory Installation and RadiologyDepartment Dr. Wahidin Sudirohusodo Hospital in Makassar from March to July, 2008. Patient made to criteria done some laboratorytest for AST and ALT examination. Data was analyzed using T-Test in SPSS for windows version 11,5. In this study we found that therewere a significant difference between non-alcoholic fatty liver degree with AST and ALT activity in cutt off 18 (p < 0,05). From this studywe could conclude that the activity of AST and ALT serum can be used to predict probability of non-alcoholic fatty liver.